1986
DOI: 10.1017/s0003356100017682
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary food intake in relation to body weight among British breeds of cattle

Abstract: Voluntary food intake and body weight were examined over 4-week intervals between 14 and 70 weeks of age in 306 females from 25 British breeds of cattle. At each age, the relationship of the natural logarithm of voluntary food intake to that of body weight was examined by linear regression both within and between breeds.Of the total variation in voluntary food intake, the proportion accounted for by body weight was extremely high between breeds (phenotypically, 0-80 or more; genetically 0-88 or more, at most a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…They found shorter grazing times in the larger animals and the exponent relating HOMI to W in the heifers and calves was 0-71, or 0-61 when the cows were included. The authors recognized the potential influence of sward characteristics on intake and the exponent of W, but under unrestricted grazing conditions it appears that the exponent is close to that found by Taylor et al (1986) to apply for growing cattle ranging from 0-17 to 0-70 of their mature size and given ad libitum access to pelleted feeds.…”
Section: Effects Of Sex and Degree Of Maturitymentioning
confidence: 62%
See 2 more Smart Citations
“…They found shorter grazing times in the larger animals and the exponent relating HOMI to W in the heifers and calves was 0-71, or 0-61 when the cows were included. The authors recognized the potential influence of sward characteristics on intake and the exponent of W, but under unrestricted grazing conditions it appears that the exponent is close to that found by Taylor et al (1986) to apply for growing cattle ranging from 0-17 to 0-70 of their mature size and given ad libitum access to pelleted feeds.…”
Section: Effects Of Sex and Degree Of Maturitymentioning
confidence: 62%
“…The most important determinant of voluntary food intake is body weight. In growing cattle, intake scales with about W 07 at any given age between 3 and 18 months (Taylor et al 1986). Under unrestricted grazing conditions, a similar exponent of W has been found (Hodgson & Wilkinson 1967).…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…This may suggest that some other physiological factor associated with the J breed, other than LW, could be responsible for their higher Gross Ee values. Greater efficiencies exhibited by J cows may reflect: (i) a greater efficiency of utilisation of ME for milk and tissue production (0.58 versus 0.48) as a consequence of a lower heat increment (L'Huillier et al 1988); and (ii) a greater ability to consume more feed per unit liveweight than F cows (Taylor et al 1986), which may be a function of larger reticulo-rumen volumes. Nagel & Piatkowski (1988;cited by Brade 1992) found that J cows had 32 litres of reticulo-rumen volume per 100 kg of body weight compared with only 23 litres for F cows.…”
Section: Feed Conversion Efficiency Parametersfriesian Versus Jersey mentioning
confidence: 99%
“…2003; 7, Jenkins & Ferrell 2002; 8, Afolayan et al. 2007; 9, Kuehn & Thallman 2010; 10, Taylor et al. 1986; 11, Jakubec et al.…”
Section: Resultsmentioning
confidence: 99%